Skin disease : diagnosis and treatment / Thomas P. Habif, James G.H. Dinulos, - Habif, Thomas P.
Get practical guidance from renowned dermatologist Dr. Thomas Habif and his expert team of co-authors in this user-friendly, focused text. Written specifically for the non-specialist, this easy-to-follow reference offers precisely the diagnostic and treatment information you need to quickly identify the 250 skin disorders you're most likely to see. It's an ideal resource for any medical practitioner who'd rather treat than refer patients with skin disease, as well as an excellent review for board preparation